Epidemiologic Characteristics of Adolescents with COVID-19 Disease with Acute Hypoxemic Respiratory Failure. (5th September 2022) - Kest, Helen; Kaushik, Ashlesha; Shaheen, Somia; Debruin, William; Zaveri, Sahil; Colletti, Mario; Gupta, Sandeep
Abstract : We report our experience of COVID-19 disease with hypoxemic respiratory failure among patients aged 12–21 years admitted to the intensive care unit at two tertiary care institutions in Northeastern and Midwestern United States. Our results showed that during the main study period that spanned the initial surge at both geographic locations, adolescents with SARS-COV-2 infection admitted to the ICU with respiratory failure were more likely to be male, black, and morbidly obese and with two or more comorbidities. The majority (79%) were admitted with COVID-19-related pneumonia and 15 developed respiratory failure; two-thirds of patients with respiratory failure (9/15, 60%) required mechanical ventilation (MV). More than two-thirds of patients (11/15, 75%) with respiratory failure were obese with BMI > 30 compared to those without respiratory failure (p < 0.0001 ), and those with BMI > 40 were 4.3 times more likely to develop respiratory failure than those with normal BMI; 40% of patients with respiratory failure had two or more pre-existing medical comorbidities. Inflammatory markers were 2–20 times higher in patients with respiratory failure (p < 0.05 ). The majority of patients on MV (7/9) developed complications, including ARDS (acute respiratory distress syndrome), acute renal injury, and cerebral anoxic encephalopathy. Patients with respiratory failure had a significantly longer length of hospital stay than patients without respiratory failure (p < 0.05 ). The majority of the admitted adolescents in the ICU received steroid treatment. None of the patients died. An additional review of a 6-month postvaccination approval period indicated that the majority of ICU admissions were unvaccinated, obese, black patients and all patients who developed respiratory failure were unvaccinated. Our study highlights and supports the need for maximizing opportunities to address vaccination and healthcare gaps in adolescents as well as promoting public health measures including correct use of masks, effective vaccination campaigns for this age group, and additional passive preventive interventions for COVID-19 disease in adolescents especially with comorbid conditions, and in minority populations.